Um sistema hiperbólico e o custo de controlabilidade para o sistema de Stokes via método da transmutação - Sousa Neto, Jose Ribeiro de (2017)
In this work, we studied the controllability cost for the Stokes system. Using the transmutation method, we show that the cost of driving the Stokes system to equilibrium at time T, is of order eC/T as T → 0+, which is of the same order of controllability of heat equation. For this, we have proved a exact controllability for the hyperbolic system with resistence term, by considering a geometric hypothesis on the control region.